Cancer penis evaluation of role of prophylactic inguinal lymph nodes dissection - Nichkaode, Prabhat B.; Agrawal, Rajendra; Kulkarni, Sayali (International Surgery Journal, 2017)
Background: Incidence of penile cancer is considerably variable across the globe; this disease is uncommon in the western world. But it is not uncommon to see the disease in Indian subcontinent. Also, it is not uncommon to see Penile growths with palpable unilateral or bilateral lymph nodes. In this retrospective observational study, we would like to present our data of 31 cases of Penile cancer with variable presentations, in terms of palpable groin lymph nodes. FNAC from palpable lymph nodes may not be diagnostic of metastasis. It is said that battle of cancer penis is either won or lost depends on how you deal with groin. It is a clear understanding that in presence of positive groin nodes Lymphadenectomy is the choice of treatment but it is unclear, how to deal with negative groin? In this study we present experience, in terms of deal with the groin lymph nodes aggressively, even when they not palpable for a better outcome after balancing the morbidity of the procedure. Aim was to evaluate the role of early prophylactic inguinal node dissection in patients with squamous cell cancer of Penis. Methods: This retrospective observational study was carried out at tertiary care teaching institute from 2003 till 2012. The clinical, investigational, operative, pathology details and follow-up data were collected from patient records. Results: Study showed data of 47 patients treated during the period from 2003 to 2012 and included 31 patients in this study, 21 patients (67.74%) presented with palpable inguinal nodes at the time of primary presentation. FNAC from these lymph nodes could prove metastasis, only in 16 patients (76.19 %). 5 patients (23.80) on FNAC had no metastasis. Remaining 10 patients were without lymph node enlargement at the time of primary presentation. Patients presented without palpable lymph nodes were offered modified inguinal block dissection. Histology showing 8 nodes positive for metastatic disease. And were FNAC was negative 4 (80 %) out of 5 patients with negative nodes shown positive for metastasis. Conclusions: This retrospective observational study concludes with fact that palpable lymph nodes in the groin, is no doubt an indication for Inguinal node dissection but even when nodes are negative on FNAC or not palpable then prophylactic lymph nodes dissection should be undertaken. Delay in inguinal lymphadenectomy in non-palpable nodes you may lose the battle on cancer penis, as many reports say that, delayed lymphadenectomy has a strong impact on the survival. The only drawback with prophylactic lymph node dissection is the associated morbidity. But with modified procedures this can be very well minimized.